2022
DOI: 10.3390/molecules27020565
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Volatile Compounds in Ten Varieties of Zingiberaceae

Abstract: Zingiberaceae plants are distributed in the tropical and subtropical regions of the world, being used in many famous medicinal materials. Meanwhile, some Zingiberaceae plants are important horticultural flowers because they are green all year round and have special aromas. To conduct an extensive investigation of the resources of Zingiberaceae plants, the volatile compounds of ten species of Zingiberaceae were extracted and analyzed by GC–MS, including Costus comosus var. bakeri (K.Schum.) Maas, Curcuma rubesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 45 publications
0
11
1
Order By: Relevance
“…Only the blend had a significant effect on the TA, and the sensory analysis intensity scores indicated no significant difference in the perceived sourness. Ogori et al [ 29 ] reported a °Brix of 9.32 and TA of 0.84 for their 80P10T10G juice, which differed from our study’s same composition formulations. However, the increase in the TSS and TA in pineapple juice may correlate with changes in the citric acid content, which can be influenced by variety, maturity, storage temperature, and post-harvest handling [ 30 , 31 ].…”
Section: Resultscontrasting
confidence: 97%
See 1 more Smart Citation
“…Only the blend had a significant effect on the TA, and the sensory analysis intensity scores indicated no significant difference in the perceived sourness. Ogori et al [ 29 ] reported a °Brix of 9.32 and TA of 0.84 for their 80P10T10G juice, which differed from our study’s same composition formulations. However, the increase in the TSS and TA in pineapple juice may correlate with changes in the citric acid content, which can be influenced by variety, maturity, storage temperature, and post-harvest handling [ 30 , 31 ].…”
Section: Resultscontrasting
confidence: 97%
“…In the hierarchical cluster dendrogram ( Figure 3 ), the ten ester volatiles formed a distinct cluster for pineapple juice. Ginger and turmeric, both members of the Zingiberaceae family, share many volatile aromas [ 17 , 29 ]. Common volatiles to both include terpenes such as 3-carene, α-terpinene, α-zingiberene, and β-sesquiphellandrene.…”
Section: Resultsmentioning
confidence: 99%
“…In the Zingiberaceae family, with approximately 53 genera and over 1200 species distributed in all tropical regions of the world, there are also rhizomatous genera such as Curcuma , well-known for their distinctive aroma and numerous bioactivities [ 85 , 86 , 87 , 88 ]. This shares certain bioactive compounds and medicinal properties with Zingiber spp [ 89 ].…”
Section: Natural Sources Of Zerumbonementioning
confidence: 99%
“…This is the basis for the use of nutraceuticals as adjuvants in these conditions. The Zingiberaceae family, comprising more than 1400 species distributed in tropical and subtropical areas, has been widely used in traditional Chinese and Indian medicine to prevent and treat numerous pathologies [ 1 , 2 ]. Plants of this family are also used as foods (spices and herbs) and to produce natural dyes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%